The events - Greig, David 1969- (Faber and Faber, 2013)
"When Claire, a priest, survives an atrocity, she sets out on a quest to answer the most difficult question of all: 'Why?' It's a journey that takes her to the edge of reason, science, politics and faith. David Greig's daring new play explores our destructive desire to fathom the unfathomable and asks how far forgiveness can stretch in the face of brutality. The Events was commissioned and first produced by Actors Touring Company in a co-production with the Young Vic Theatre, Schauspielhaus Wien and Brageteatret. It premiered at the Traverse Theatre, Edinburgh, in August 2013, where it was awarded a Scotsman Fringe First and the Carol Tambor Best of Edinburgh Award."